TEXTUAL PRODUCTION AND AUTHORSHIP IN VIRTUAL LEARNING ENVIRONMENT: A DIALOGICAL WRITING - Sousa, Claudemir [UNESP] (Univ Fed Minas Gerais, Fac Letras, 2017)
The possibilities offered by the technological tools for the production of text greatly affect the conception we have of writing and authorship. In this article, we aim at discussing a dialogical conception of writing and authorship, by analyzing a virtual written interaction made by students of a public university in the state of Sao Paulo. This discussion is anchored in the theoretical assumptions of Mikhail Bakhtin and his contemporary interlocutors about the theoretical categories of author and dialogism, as well as on studies about the impact of the use of technological tools in textual production on the relationship with writing and the authorship, especially in virtual learning environments. We conclude that writing in the Virtual Learning Environment occurs in a dialogical process between students, teacher(s) and other texts, occurring convergences or divergences when students take the place of author who organizes voices.
Keywords: writing; authorship; dialogism; virtual learning environment